Aedes aegypti Aag-2 Cell Proteome Modulation in Response to Chikungunya Virus Infection - Vasconcellos, Anna Fernanda; Melo, Reynaldo Magalhães; Mandacaru, Samuel Coelho; de Oliveira, Lucas Silva; de Oliveira, Athos Silva; Moraes, Emily Caroline dos Santos; Trugilho, Monique Ramos de Oliveira; Ricart, Carlos André Ornelas; Báo, Sônia Nair; Resende, Renato Oliveira; Charneau, Sébastien (Frontiers in Cellular and Infection Microbiology, 2022)
Chikungunya virus (CHIKV) is a single-stranded positive RNA virus that belongs to the genus Alphavirus and is transmitted to humans by infected Aedes aegypti and Aedes albopictus bites. In humans, CHIKV can cause painful symptoms during acute and chronic stages of infection. However, the virus-vector interaction has characteristics that allow a persistent infection, not disturbing the mosquito fitness. Here, we aimed to clarify aspects of CHIKV infection in Ae. aegypti Aag-2 cells through label-free quantitative proteomic analysis and transmission electron microscopy (TEM). We used MOI 0.1 to infect Aag-2 cells in biological triplicates over 48 h. TEM images show a high load of intracellular viral cargo at 48 hpi, as well as an elongated unusual mitochondria morphology that might indicate a mitochondrial imbalance. Moreover, a total of 196 Ae. aegypti protein groups were up or down-regulated upon infection, related to protein synthesis, energy metabolism, signaling pathways and apoptosis. These regulated Aag-2 proteins might have roles in antiviral and/or in pro-viral mechanisms during CHIKV infection, to support the balance between viral propagation and the survival of host cell, leading to the persistent infection.